Rajasthan's role in the struggle of 1857 - Khadgawat, Nathu Ram (Bikaner Directorate, Rajasthan State Archives, 2008)
The Upheaval of 1857, which appeared at first 'a small cloud-no bigger than a man's hand' grew bigger and bigger till at last it overwhelmed the British East India Company with ruin. During this period of storm and stress, the entire Princely Order of Rajasthan 'proved their staunch fidelity to the Paramount Power and almost all the rulers 'clustered round the waning fragments of the British Empire. Maharana Swaroop Singh 'exerted his great influence as the acknowledged Head of all the Rajput princes on the side of the British by advising all, who applied to him by letter or by accredited ministers specially deputed for counsel at the crisis, to stand firm in their allegiance to the British Government." The Maharaja of Karowli sent levies in British support, drove out of his territory the Gwalior rebels and sent a detachment of 800 (followed by a re-inforcement of 1500) to Kotah with a view to rescue the Maharao who had been reduced by the rebels to the status of a virtual prisoner. He even 'issued a proclamation to his subjects, pointing out in strong language the delusion' under which the mutineers had been labouring and called upon his people not only not to join the rebels but to help him also in fighting for the British Government. Maharaja Ram Singh of Jaipur remained absolutely loyal to the British cause even amidst strongest temptations. Despite the revolt of his troops, the Nawab of Tonk supported the British even at 'considerable personal risk and pecuniary loss. Maharaja Takhat Singh of Jodhpur, though rendered totally powerless to aid the British as a result of the anti British revolts of his refractory chiefs, did not lose any opportunity to show his pro-British zeal. It was, however, only in case of the rulers of Kotah and Bundi that the A.G.G. could find an opportunity to make certain adverse remarks in his report on the Mutiny in Rajasthan.
Keywords: 1857 revolt